EU Publics Express Doubts About Union Benefits. - United States. Department of State. Office of Research.; Teare, Mark. (Tufts University. Tisch Library., 2019)
Results from Office of Research polls in western Europe show that public opinion on the EU is as mixed and complicated as the myriad of challenges stemming from the implementation of a European vision among diverse nation-states.; Opinion Analysis M-324-00